Optimization of chanterelle mushroom drying kinetics under heat pump dryer using Taguchi design method - Mecha, Peter; Zhu, Rui; Zhang, Jiayu; Awuah, Emmanuel; Soomro, Shakeel Ahmed; Chen, Kunjie (International Journal of Agricultural and Biological Engineering, 2024)
The optimum drying conditions with regard to minimum color changes, high rehydration ratio and drying rate for chanterelle mushrooms is inadequately known. To address this problem, drying kinetics for chanterelle mushroom samples with sizes of 20 mm×20 mm×20 mm cube, 20 mm×20 mm×30 mm cuboid, and Ø40 mm×20 mm cylindrical shape were experimented. Drying air temperatures of 40°C, 48°C, and 56°C at superfluous humidity and velocity of 2.2 m/s were used. Initial color pixels for each sample were determined using Note 8 Pro Xiaomi smartphone camera and image processing tool in Matlab R2019a. Triplicate experimentation was done based on L9 Taguchi orthogonal arrays with drying rate, specific moisture extraction rate, color change, and rehydration ratio being the response parameters. The drying rate increased from 1.1174 g/g∙min to 1.3478 g/g.min as the temperature rose from 40°C to 56°C. The mushroom cube had the highest drying rate of 1.2860 g/g∙min while the cylindrical shape had the lowest rate of 1.1764 g/g∙min. Similarly, SMER increased from 0.006326to 0.01327 g/kWh with the temperature rise. Contrary, SMER decreased from 0.00692 to 0.01363 g/kWh in cylinder to cube respectively. Color change was highest at 40°C (13.49) and lowest at 56°C (11.94). The mushroom cube had the lowest color change of 9.28 on average when compared to other shapes. Rehydration ratio was highest at 56°C (3.824) as compared to 48°C and 40°C. Additionally, the mushroom cube had the highest rehydration ratio of 4.55 on average as compared to other shapes. Temperature variation significantly influenced the drying rate and SMER. However, temperature variation had insignificant differences in color change and rehydration ratio. Mushroom shape variation had a significant difference in all the response variables tested. Conclusively, mushroom cubes at the drying temperature of 56°C gave optimized drying conditions for chanterelle mushrooms with minimal quality deviations. Thus, chanterelle mushrooms can be sliced into cubes to allow quick drying rate, better SMER, rehydration ratio, and have minimal color change. Keywords: optimization, chanterelle mushrooms, drying kinetics, heat pump dryer, Taguchi designDOI: 10.25165/j.ijabe.20231606.6408Citation: Mecha P, Zhu R, Zhang J Y, Awuah E, Soomro S A, Chen K J. Optimization of chanterelle mushroom drying kinetics under heat pump dryer using Taguchi design method. Int J Agric & Biol Eng, 2023; 16(6): 273–279